THE INFLUENCE OF ROLE STRESS ON ORGANIZATIONAL COMMITMENT IN CLASS IIA CURUP CORRECTIONAL INSTITUTION - Ahmad Muchlis Surya Darmawan; Padmono Wibowo (Universitas Nusa Cendana, 2026)
This study aims to analyze the effect of role stress on organizational commitment among employees at Class IIA Correctional Institution Curup. Role stress in this study is viewed through three main dimensions: role ambiguity, role conflict, and role overload, while organizational commitment is reflected through affective, continuance, and normative commitment. The research is motivated by several workplace conditions such as high workloads, uneven employee distribution, overcrowded inmate populations, and unclear role definitions, which can potentially increase role stress and reduce employee loyalty to the organization. This research uses a quantitative approach through a survey method, where data were collected from employees using questionnaires and analyzed using simple linear regression. The results show that role stress has a negative influence on organizational commitment. This means that higher levels of role stress tend to reduce employees’ commitment to the organization. These findings emphasize the importance of managing workplace stress through clearer role definitions, fair workload distribution, and stronger organizational support in order to maintain employee loyalty and productivity. Keywords: Role Stress; Organizational Commitment; Role Ambiguity; Role Conflict; Workload; Correctional Institution